Impelementasi pendididkan sex pada anak usia dini di sekolah - Sarah Emmanuel Haryono; Henni Anggareni; Siti Muntomimah; Didik Iswahyudi (Universitas Tribhuwana Tunggadewi, 2018)
Sex education in Indonesia is still a controversy, there are still many community members who have not agreed on sex education at home or at school. In general, the public view of sex education is considered